"Nano effects": a review on nanoparticle-induced multifarious systemic effects on cancer theranostic applications. Issue 22 (5th October 2022) - Ravichandran, Gayathri; Yadav, Dokkari Nagalaxmi; Murugappan, Sivasubramanian; Sankaranarayanan, Sri Amruthaa; Revi, Neeraja; Rengan, Aravind Kumar
Abstract : The advent of nanotechnology has broadened the scope of technological advances in both medical and industrial applications. Abstract : The advent of nanotechnology has broadened the scope of technological advances in both medical and industrial applications. Nanotechnology has paved the way for cancer diagnosis and therapy with the conceptual inauguration of this field by Nobel laureate Richard Feynman. Understanding how it works and how it interacts with biological systems has been extensively researched, which is critical in its application. When the size of biomaterial systems is reduced from bulk to nano, the surface reactivity increases at the atomic and subatomic scales. Because extraordinary "quantum effects" are pronounced when materials are reduced to nano sizes, understanding the nano-mediated effects is critical. This review introduces and elaborates on the various effects induced by nanoparticles, particularly in the field of cancer treatment.